Estrogen deficiency inducing shifted cytokines profile in bone marrow stromal cells inhibits Treg cells function in OVX mice - Zeng, Q-M; Liu, D-C; Zhang, X-C; Wu, J-P; Ding, L; Meng, D-H; Zhang, J (Cellular and Molecular Biology, 2015)
The study aims to reveal the effect of estrogen deficiency on Treg cells population in bone marrow in the development of osteoclastogenis with comparing the differences about Treg cells phenotypes and cytokines related with the homeostasis and functions maintenance of Treg cells in bone marrow in OVX mice and health control group. Wide-type C57BL/6 mice were operated OVX to mimic estrogen deficiency in PMO women. Treg cells population and their surface markers expressions were detected by flow cytometry. Cytokines profiles in bone marrow with examined by real-time PCR and ELISA analysis. Signal pathways and key modulators responsible to inflammatory cytokines expressions in bone marrow stromal cells were also detected with using western blotting. Estrogen deficiency in OVX mice decreased Treg cells and their functions, and cytokines profile in bone marrow were found shifted in bone marrow when compared with control group. Consistent to these observations, signal pathways in bone marrow stromal cells were reported altered by estrogen deficiency in our model. Estrogen deficiency effects Treg cells population and their functions in OVX mice with altering cytokines profile in bone marrow stromal cells.